PENINGKATAN PENDAPATAN KELUARGA MELALUI PELATIHAN PENGOLAHAN PRODUK BERBASIS IKAN LAUT - Barika -; Ratu Eva Febriani; Yusnida - (Universitas Bengkulu, 2018)
The purpose of the community service activities are society, especially women as housewife, able to diversify its business through the business of making fish balls and fish tekwan which have high economic value. From this extension activity, women are able to increase their family income by doing business at home. Community service activity method is to conduct discussions and question and answer session conducted while delivering the training material. In addition there is a demonstration method of making meatballs and “tekwan”. Berdasarkan training outcomes mother-housewife who became a trainee is able to develop products processed marine fish feed marine fish tekwan the meatballs and marine fish. Keywords: housewife, income, sea fish products